2005
DOI: 10.1111/j.1469-8137.2005.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition‐ and resource‐mediated tradeoffs between growth and defensive chemistry in trembling aspen (Populus tremuloides)

Abstract: Summary• Costs of defense are thought to maintain genetic variations in the expression of defense within plant populations. As with many plant species, aspen exhibits considerable variation in allocation to secondary metabolites. This study examined the independent and interactive effects of genotype, soil fertility and belowground competition on defensive chemistry and growth in trembling aspen ( Populus tremuloides ).• Four aspen genotypes were grown with high and low soil fertility, and with and without roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 62 publications
8
102
2
Order By: Relevance
“…Our results confirm those obtained by (Ormeño et al, 2007a,b) who observed, for P. halepensis, under experimental conditions with intra-specific competition, an increase of terpenoid emission at low or medium competition level (when nutrients are available) and a decrease of terpenoid emission at high competition level (at low nutrient concentration). These results show that moderate competition can increase the concentration of some allelochemicals, as stated by An et al (2003), by modifying the relative importance of the metabolic pathways in relation to each other, as observed by Donaldson et al (2006). Nonetheless, our results on the competition effect on allelochemical production and biomass fit for the most part with the Growth Differentiation Balance Hypothesis which states that secondary metabolite production, such as that of phenolic compounds, and growth are limited under low resource availability (Herms and Mattson, 1992).…”
Section: Discussionsupporting
confidence: 59%
“…Our results confirm those obtained by (Ormeño et al, 2007a,b) who observed, for P. halepensis, under experimental conditions with intra-specific competition, an increase of terpenoid emission at low or medium competition level (when nutrients are available) and a decrease of terpenoid emission at high competition level (at low nutrient concentration). These results show that moderate competition can increase the concentration of some allelochemicals, as stated by An et al (2003), by modifying the relative importance of the metabolic pathways in relation to each other, as observed by Donaldson et al (2006). Nonetheless, our results on the competition effect on allelochemical production and biomass fit for the most part with the Growth Differentiation Balance Hypothesis which states that secondary metabolite production, such as that of phenolic compounds, and growth are limited under low resource availability (Herms and Mattson, 1992).…”
Section: Discussionsupporting
confidence: 59%
“…The EICA hypothesis, one of the central tenets of invasion biology theory, predicts that exotic plant species suffer less damage by herbivores in their introduced ranges and they might thus reallocate fewer resources to defence and more to growth and reproduction. In addition to the differential herbivore pressures, this outcome arises because plant defence/resistance traits are energetically expensive to produce and maintain, and therefore it is commonly assumed that resistance and fitness traits trade-off with each other (Messina et al, 2002;Donaldson et al, 2006;Sampedro et al, 2011a). The existence of such trade-offs between defence and fitness traits may explain why exotic plant species are usually more vigorous in non-indigenous habitats (usually with reduced load of enemies) than in their natural range.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming that the production of plant defences is costly in terms of growth and fitness, current theories on the evolution of plant resistance predict the existence of evolutionary trade-offs (negative genetic correlations) between resistance and fitness traits (Messina et al, 2002;Donaldson et al, 2006;Sampedro et al, 2011a), and between different resistance traits (reviewed by Koricheva et al (2004)). The existence of these trade-offs may severely constrain the invasion success of plant populations in non-indigenous habitats, as trade-offs limit the simultaneous change of negatively correlated traits (Orians and Ward, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental defoliation is a well-developed technique to examine carbon limitations in field settings (Li et al, 2002;Körner, 2003;Snyder and Williams, 2003;Markkola et al, 2004;Handa et al, 2005;Landhausser and Lieffers, 2012) and trade-offs in allocation to growth versus defense (Jones et al, 2004;Osier and Lindroth, 2004;Donaldson et al, 2006). We performed a repeated defoliation experiment of mature trembling aspen ramets with the goal of inducing carbon stress/starvation ("carbon stress" defined here as a combination of source limitation [removal of photosynthetic tissue] and sink enhancement [regrowth of successive canopies]; Handa et al, 2005).…”
mentioning
confidence: 99%